The in/visible line. The border, territory of experience - Alonso Riveiro, Mónica; Ferreira, Susana (Anales de Historia del Arte, 2020)
In the last years, border studies have developed the concept of bordering, which describes borders not as immutable topographies but rather as processes. This invites us to think about them ‘beyond the line’, showing border spaces as changing zones, always in construction. In parallel, critic cartography and artistic practices have developed representations in which border spaces reveal an identic dynamic, fluid or ‘faltering’ character. Based on the double optics of border studies and artistic practices and through a visual journey along different representations of the border, the present text will try to dismantle some preconceived ideas about them, question its visibility and invisibility and explore its dynamic of faltering character. Above all reflect on the multiple ways in which it determines the life of individuals and the print it leaves on them, on its images and therefore on their (our) memory. It is about making visible an alternative cartography, in which domestic photography is intrinsic with artistic practices and were border spaces are not only places of dominance but of reconstruction, of potentiality, from which to assume one’s own condition, and starting from it, reconfiguring the real.